MiR-184 expression is regulated by AMPK in pancreatic islets - Martinez-Sanchez, A; Nguyen-Tu, M; Cebola, I; Yavari, A; Marchetti, P; Piemonti, L; de Koning, E; Shapiro, A; Johnson, P; Sakamoto, K; Smith, D; Leclerc, I; et al. (Federation of American Society of Experimental Biology, 2017)
AMPK is a critical energy sensor and target for widely used antidiabetic drugs. In β-cells, elevated glucose concentrations lower AMPK activity, and the ablation of both catalytic subunits (βAMPKdKO mice) impairs insulin secretion in vivo and β-cell identity. MicroRNAs (miRNAs) are small RNAs that silence gene expression that are essential for pancreatic β-cell function and identity and altered in diabetes. Here, we have explored the miRNAs acting downstream of AMPK in mouse and human β-cells. We identified 14 down-regulated and 9 up-regulated miRNAs in βAMPKdKO vs. control islets. Gene ontology analysis of targeted transcripts revealed enrichment in pathways important for β-cell function and identity. The most down-regulated miRNA was miR-184 (miR-184-3p), an important regulator of β-cell function and compensatory expansion that is controlled by glucose and reduced in diabetes. We demonstrate that AMPK is a potent regulator and an important mediator of the negative effects of glucose on miR-184 expression. Additionally, we reveal sexual dimorphism in miR-184 expression in mouse and human islets. Collectively, these data demonstrate that glucose-mediated changes in AMPK activity are central for the regulation of miR-184 and other miRNAs in islets and provide a link between energy status and gene expression in β-cells.-Martinez-Sanchez, A., Nguyen-Tu, M.-S., Cebola, I., Yavari, A., Marchetti, P., Piemonti, L., de Koning, E., Shapiro, A. M. J., Johnson, P., Sakamoto, K., Smith, D. M., Leclerc, I., Ashrafian, H., Ferrer, J., Rutter, G. A. MiR-184 expression is regulated by AMPK in pancreatic islets.